Peran Forum Kerukunan Umat Beragama dalam Memelihara Toleransi Beragama Kota Salatiga Tahun 2018 - Titin Nuryani; Ahmad Taufiq (Journal of Politic and Government Studies, 2019)
The inter-religious harmony established in Salatiga City is inseparable from the role of civil society. The respect for each other, which has become a habit for the community since the beginning, made Salatiga one of the most populous cities in Indonesia according to SETARA Institute. So this study aims to determine the benchmark of the success of religious tolerance according to Salatiga City itself, the reality of intertwined religious tolerance, and the factors that support religious tolerance.The research method used is descriptive qualitative where data collection techniques in the form of interviews, documentation, and direct participation. The data is then analyzed using data source triangulation.The results of the study indicate that the success of Salatiga as one of the most populous cities in Indonesia from 2015 to 2018 due to the habit of the Salatiga City people who have always been conducive to conducting various interfaith activities, supported by the Religious Harmony Forum (FKUB). The obstacles encountered were awareness of illicit organizations that caused intolerance.Keywords: Civil Society, religious tolerance, FKUB